La protección de los consumidores en la Unión Europea: ¿mito o realidad? - Moráis Carvalho, Jorge (2023)
During the last years, the consumer’s protection turns in one of the politic decision process priorities of European Union. However, their bounds are evident: linguistic diversity, different juridical cultures, the kind of adopted rules and the questions ignored by the directives but essential for the effective application of the consumer’s protection regime. The objective of these rules is not clear because, if the principle of consumer’s protection is today clearly consecrated in the communitarian law, in a lot of times it is used like an enforcement instrument for the Common Market.